Language and Social Interaction at Home and School. - Caronia, Letizia (Amsterdam/Philadelphia : John Benjamins Publishing Company, 2021)
The volume provides new multidisciplinary insights and updated empirical data on the process through which cultures, identities, and knowledge are brought into being through the everyday dialogues that animate children's life at home and school.
9. Facilitating children's elicitation of interlaced narratives in classroom interactions -- 1. Introduction -- 2. Data -- 3. The analysis of interlaced narratives in classroom interactions: Theoretical background -- 3.1 Facilitation, agency and epistemic authority -- 3.2 Structures of positioning -- 3.3 The analysis -- 4. Analysis of facilitation supporting children's agency as elicitation of new narratives -- 4.1 Questions and invitations -- 4.2 Leaving the floor to children's elicitation of new narratives -- 4.3 Enhancing interruptions as narratives -- 5. Facilitation that treats children's interruptions as obstacles to narrative -- 5.1 Providing quick feedback and going back to the interrupted narrative -- 5.2 Providing feedback to critical contributions -- 5.3 Ignoring the interruptions -- 6. Conclusions -- References -- Anchor 178 -- Appendix -- Transcription conventions -- 10. Student-teacher e-mail interaction as asynchronous dialogue in an academic setting -- 1. Introduction -- 2. Theoretical background -- 3. Methodology -- 4. Data and discussion -- 4.1 E-mail structure -- 4.2 Process types -- 5. Conclusion -- References -- Contributors -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Social interaction; Electronic books